Unveiling the Shadow: Theorizing the Impact of Narcissistic Leadership on Sales Teams - Bullemore, Jorge (International Review of Management and Marketing, 2024)
This study investigates the dual nature of narcissistic leadership within sales teams, revealing its potential to both inspire ambitious goals and undermine team cohesion and performance. By integrating a comprehensive literature review, the research outlines the characteristic behaviors of narcissistic leaders, such as arrogance and a lack of empathy, and their impact on team dynamics, including reduced cohesion, increased conflict, and impaired team performance. The paper proposes strategies to mitigate these negative effects, such as leadership development programs, team-based performance evaluations, and fostering a culture of empathy. It highlights the importance of understanding and addressing the complexities of narcissistic leadership to cultivate healthier, more productive team environments. The findings call for further research into the long-term effects of narcissistic leadership and the development of effective management strategies.